Volunteer human subjects’ understandings of their participation in a biomedical research experiment - Morris, Norma; Bàlmer, Brian (Social science & medicine (1982), 2006)
The paper focuses on how volunteer human subjects in research understand their own participation in experimentation. We ask how they view their own role, the experimental setting, and how they articulate their understanding of the researcher–subject relationship. The empirical basis of the study is participant-observation and qualitative semi-structures interviews with volunteers in an experimental setting far removed from the more commonly studied randomised control trial (RCT), namely, the early stage testing of a prototype instrument for breast imaging. Analysis of this empirical data leads us to conclude that research subjects do not conform solely to one or other of the models of the researcher–subject relationship suggested in the literature. Rather, the interaction needs to be considered as a social situation which volunteer subjects actively negotiate in real time. They move through multiple roles and identities as part of the navigation through unfamiliar social territory, in order to establish a relationship in which they can feel socially comfortable and appropriately valued.